Genetic diversity in Sesamum indicum L. - Bhattacharjee, Maini; Iqbal, Adil; Singha, Sanjana; Nath, Disharee; Prakash, SH; Dasgupta, Tapash (Bangladesh Journal of Botany, 2019)
Sesame (Sesamum indicum L.), is the most ancient and important oilseed crop for its good quality edible oil. Much variability among genotypes exists in sesame which helps the breeder to choose good parents in hybridization. In the present study, 30 genotypes were studied for 12 morphological traits. Correlation analysis exhibited that seed yield per plant was positive and significantly correlated with capsules per plant and 1000-seed weight. Apart from morphological data, initial genotyping was conducted for 32 microsatellites but finally only polymorphic primers were selected for genetic diversity study. Estimated polymorphism information content (PIC) value ranged from 0.07 to 0.87 and SSR 24 showed to be highest at 0.87. The dendrogram was constructed using the software NTSYS Pc Ver. 2.20 based on morphological and molecular data. Geographical diversity did not corroborate with genotypic diversity as the cluster composition revealed that genotypes belonging to different geographical origin grouped in the same cluster.